Studies on the Ecological Competence of Civic Education in Primary Schools - Feriandi, Yoga Ardian; Budimansyah, Dasim; Komalasari, Kokom (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2021)
The development of the world of technology has provided many changes in the pattern of human life, including influencing environmental phenomena that have an impact on the way of life of citizens. To prevent environmental destruction. So ecological education is one of the efforts to continue the effort to create citizens who care about the environment with their environmental characteristics. This study aims to examine the ecological competence of elementary school students through civic education in building awareness of the environment. The approach used in this research is qualitative with the literature study method. The results of the analysis and study in this study indicate: 1) the competence of knowledge and ecological strategies of elementary school students is formed through civic education, 2) elementary school students can act on environmental issues, 3) elementary school students have the quality to address environmental issues through civic education. So that the conclusion in this study is that the ecological competence of elementary school students can be formed through civic education, the output of which is that these students have environmental skills and character in utilizing their environment.